2020
DOI: 10.1088/1755-1315/429/1/012043
|View full text |Cite
|
Sign up to set email alerts
|

Bigeye tuna fishing ground analysis using oceanographic features in Eastern Indian Ocean off Southern Java

Abstract: The Eastern Indian Ocean off Southern Java is one of the bigeye tuna fishing hotspots and has a fishing potential of 27%. Analyses of bigeye tuna fishing areas focus on the South Java-Bali waters at coordinates of 105°-120 ° E and 5 ° - 20 ° S. Oceanographic parameters affect the habitat of Bigeye tuna. Sub surface temperature is an important and major factor in fishing layers. Time series of sub surface temperature data from 2005-2017 was used as an input for the analysis of the fuzzy inference system method.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
2
2
Order By: Relevance
“…The final environmental factors used in our best model included T0, T50, T100, T300, T500, S100, S200, S400, D0, D50, D100, D200, D500, chl-a, WS, EKE, and MLD. The environmental factors were This is inconsistent with some literatures that mentioned the bigeye tuna preference habitat at depth of 150-250 m (Bigelow et al, 2002;Dewi et al, 2020). This may be related to water characteristics in our study area.…”
Section: Analysis Of the Environmental Factorscontrasting
confidence: 98%
See 1 more Smart Citation
“…The final environmental factors used in our best model included T0, T50, T100, T300, T500, S100, S200, S400, D0, D50, D100, D200, D500, chl-a, WS, EKE, and MLD. The environmental factors were This is inconsistent with some literatures that mentioned the bigeye tuna preference habitat at depth of 150-250 m (Bigelow et al, 2002;Dewi et al, 2020). This may be related to water characteristics in our study area.…”
Section: Analysis Of the Environmental Factorscontrasting
confidence: 98%
“…In this study, we found that temperatures at the depth of 150 m have little correlation with CPUE. This is inconsistent with some literatures that mentioned the bigeye tuna preference habitat at depth of 150–250 m (Bigelow et al, 2002; Dewi et al, 2020). This may be related to water characteristics in our study area.…”
Section: Discussioncontrasting
confidence: 79%
“…Based on the results of fishermen's interviews, bigeye tuna is only caught during the full moon. This can be reinforced by the statement (Dewi et al 2020) [5] that tuna, which are predators that are positive phototaxis, need light to find food, therefore at night, the tuna will rise to the surface 0-100m to look for food. Thus, during the full moon, the light entering the waters will be brighter than the crescent moon.…”
Section: Resultsmentioning
confidence: 99%
“…Although many researchers have focused on South Java upwelling, studies o f upwelling comparisons in the shelf area, particularly by analyzing the upwelling index based on Chl-a, wind, and SST, have not yet been conducted. Dewi et al (2020) used only UISST to investigate the South Java upwelling characteristics during ENSO. Naulita et al (2020) analyzed the South Java Upwelling Index based on wind and SST in the region between 106 and 114˚E.…”
Section: Introductionmentioning
confidence: 99%